2022
DOI: 10.2147/ijn.s355131
|View full text |Cite
|
Sign up to set email alerts
|

Nano Silver-Induced Toxicity and Associated Mechanisms

Abstract: Nano silver is one of the most widely used engineering nanomaterials with antimicrobial activity against bacteria, fungi, and viruses. However, the widespread application of nano silver preparations in daily life raises concerns about public health. Although several review articles have described the toxicity of nano silver to specific major organs, an updated comprehensive review that clearly and systematically outlines the harmful effects of nano silver is lacking. This review begins with the routes of expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 92 publications
0
19
1
Order By: Relevance
“…The different effects exerted by AgNO 3 and AgNPs suggested that silver in the form of nanoparticles might solely enter the mitochondria or nucleus and induce the expression of TFAM and PGC-1α, leading to protective effects on myocardial cells. It is of interest that many published articles stated that exposure of cells to AgNPs can cause mitochondrial damage such as mitochondrial swelling, disrupting mitochondrial membrane potentials and leading to mitochondrial pathway-induced apoptosis ( 53 ) but we found the opposite effects in our study. We speculate that the green synthesized method of our AgNPs formulation by using alginate may contribute to its beneficial effects ( 54 ).…”
Section: Discussioncontrasting
confidence: 61%
“…The different effects exerted by AgNO 3 and AgNPs suggested that silver in the form of nanoparticles might solely enter the mitochondria or nucleus and induce the expression of TFAM and PGC-1α, leading to protective effects on myocardial cells. It is of interest that many published articles stated that exposure of cells to AgNPs can cause mitochondrial damage such as mitochondrial swelling, disrupting mitochondrial membrane potentials and leading to mitochondrial pathway-induced apoptosis ( 53 ) but we found the opposite effects in our study. We speculate that the green synthesized method of our AgNPs formulation by using alginate may contribute to its beneficial effects ( 54 ).…”
Section: Discussioncontrasting
confidence: 61%
“…Various bone-filling materials containing antimicrobial components were also proposed in the literature, with the purpose being to prevent perioperative infections. Silver nanoparticles are one of the choices [ 19 ]; however, their long-term safety is still a matter of debate [ 20 ]. Chitosan [ 4 ] and its quaternized derivative [ 21 ] were also reported to exhibit antibacterial properties and thus may serve as a bioactive component of the scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility of implants is a crucial criterion for their biomedical application. In the case of silver-containing implants, the release of Ag may cause cytotoxicity, which is attributed to the generation of ROS, destabilization of the cell membrane, and inactivation of essential enzymes. , The cell viability of pure PICN and Ag@PL NPs/PICN samples was assessed in vitro employing two different cell models, HaCaT and BJ5ta, which are immortalized cell lines from adult human skin with keratinocyte and fibroblast-like morphology, respectively. The culture media previously pre-incubated with Ag@PL NPs/PICN and PICN samples for 24 h or 7 days were used to grow the cells for 24 h, while a fresh medium that has not been in contact with the samples was used to grow control cells.…”
Section: Resultsmentioning
confidence: 99%